Tinjauan Literatur Sistematis: Tes Diagnostik Tiga Tingkat untuk Mengidentifikasi Kesalahpahaman dalam Kimia - Beatrice Ruth Nathania Simanjuntak; Wiji Wiji; Tuszie Widhiyanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study presents a literature review on the use of the three-tier diagnostic test in identifying students’ misconceptions in chemistry and offers insights into its effectiveness in educational evaluation. A literature review of studies from 2019 to 2024 shows that 71.43% of these tests use close-ended questions due to their efficiency in terms of time, cost, and data analysis, compared to 28.57% that use open-ended questions. Research findings indicate that this test has successfully identified misconceptions in various chemistry topics, such as equilibrium, chemical bonding, ionization energy, and acids-bases. The ability of the three-tier diagnostic test to detect misconceptions makes it an effective tool for improving students’ conceptual understanding. The findings indicate that the three-tier diagnostic test has been widely used to uncover students’ conceptual difficulties across various chemistry topics. Its use has shown promise in supporting more accurate and in-depth assessments compared to traditional evaluation methods. The review suggests that this type of diagnostic testing can enhance the quality of formative assessments and contribute to improved instructional planning.